Synthesis of a Dysprosium(III) Complex with a Hexadentate Amine Ligand - Cristina González-Barreira; Julio Corredoira-Vázquez; Ana M. García-Deibe; Matilde Fondo (Chemistry Proceedings)
The use of polydentate macrocyclic Lewis bases is a way to contribute to determine the coordination number of metal complexes. In this sense, hexadentate N6 donors can help to achieve lanthanoid complexes with coordination number 8. But the geometry of these complexes depends on the flexibility of the bases. Accordingly, in this communication we present the synthesis and crystallographic characterization of the dysprosium complex [DyLN6Cl2]Cl·2H2O, where LN6 is a flexible hexaaza donor.